The postmodern ethics of global capitalism - SUSANU, Cristina Gabriela (Annals of Spiru Haret University. Economic Series, 2011)
Global capitalism constitutes a concept surrounded by contention and controversy, fact which is evidenced by the abundance of studies regarding it, and probably the main feature which is nowadays questioned is its moral behaviour. The present study intends to provide an opposite explanation regarding the ethics of global capitalism by associating it with the contemporary movement of post-modernity. The aim of this paper is to demonstrate that global capitalism, since it reflects societies’ ethics, cannot be intrinsically good or bad, but morally ambivalent, the determination of global capitalism to be more unprejudiced depending on the willingness of individuals to be moral.